2022
DOI: 10.1038/s41387-022-00211-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of pancreas to improve hyperglycemia in STZ-induced diabetic rats by thiamine disulfide

Abstract: Background The present study investigated the effect of thiamine disulfide (TD) on the pancreas in terms of hyperglycemia improvement and insulin sensitivity increase in diabetic male rats. We also aimed to study the function of Pdx1 (pancreatic and duodenal homeobox 1) and Glut2 (glucose transporter 2) genes in pancreatic tissue. Methods Type 1 diabetes was induced through injection of 60 mg/kg streptozotocin (STZ). The diabetic rats were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…We challenged young, middle-aged, and old Ghsr-βKO mice using a single high dose of STZ to induce acute β-cell injury. A single injection of high-dose STZ (60-65 mg per kg body weight) has been shown to induce inflammation through oxidative stress [81][82][83]. We found that aged mice were less responsive to STZ, so we utilized a single injection of a higher dose of STZ (150 mg per kg body weight) to induce pancreatic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We challenged young, middle-aged, and old Ghsr-βKO mice using a single high dose of STZ to induce acute β-cell injury. A single injection of high-dose STZ (60-65 mg per kg body weight) has been shown to induce inflammation through oxidative stress [81][82][83]. We found that aged mice were less responsive to STZ, so we utilized a single injection of a higher dose of STZ (150 mg per kg body weight) to induce pancreatic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Thiamine has been implicated in T2DM and it was reported that T2DM patients have reduced levels of thiamine. Thiamine is involved in insulin synthesis and secretion 59 and reversal of hyperglycemia-induced endothelial dysfunction 60 among others 61 . However, its effect on RBP4 is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four rats were treated with a single dose of streptozotocin (STZ) (Sigma-Aldrich, St. Louis, MO, USA) (60 mg/kg, i.p.) freshly dissolved in 0.1 mM sodium citrate buffer adjusted to pH 4.5 [ 27 ]. After injection, a 5% sucrose solution was provided for 48 h to avoid hypoglycemic shock.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, twenty-four rats were treated with a single dose of 0.1 mM sodium citrate buffer as a vehicle for the non-diabetic groups. Blood was obtained from the rat tail vein on the fifth day to measure fasting blood glucose (FBG) levels using a glucometer (ACCU-Chek Performa, Basel, Switzerland) to confirm each rat’s diabetic stage (250 mg/dL) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%